Molecular identification of fungi from tissue samples - Sabino, Raquel (2022)
Tissue samples from patients with suspected invasive fungal disease (IFD) should be examined not only by mycological culture but also by microscopy and specific fungal stains should be included. For histopathological diagnosis of fungal infection is required deep knowledge about fungal morphology in tissue and also about the various reactions of the tissue in response to that infection. Highly experienced histopathologists are therefore essential to detect fungal structures and also to recognize tissue reactions associated with IFD, distinguishing them from staining artifacts. This presentation discusses different molecular methods applied to the diagnosis of invasive fungal infections. These methods may help to circunvent some constraints of histology and cultural methods.